2021
DOI: 10.3390/v13071241
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Caudovirales Phages on Humoral Immunity in Mice

Abstract: Bacteriophages are promising antibacterial agents. Although they have been recognized as bacterial viruses and are considered to be non-interacting with eukaryotic cells, there is growing evidence that phages may have a significant impact on the immune system via interactions with macrophages, neutrophils, and T-cell polarization. In this study, the influence of phages of podovirus, siphovirus, and myovirus morphotypes on humoral immunity of CD-1 mice was investigated. In addition, tissue distribution of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…However, although the presence of phage-specific antibodies with neutralizing capacity, in particular IgG2a and IgG2b, was detected after repeated intraperitoneal applications of an A. baumannii -specific phage cocktail in naïve mice, this did in fact not negatively affect the efficiency of the phages in a wound infection model [ 60 ]. Antibody formation and neutralizing capacity depend on the phage type, especially the capsid and tail protein composition; therefore, phages vary in immunogenicity and can induce different antibody responses [ 58 , 59 , 67 ]. In a murine study, Chechushkov et al [ 67 ] found that phages with podovirus morphotype were non-immunogenic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, although the presence of phage-specific antibodies with neutralizing capacity, in particular IgG2a and IgG2b, was detected after repeated intraperitoneal applications of an A. baumannii -specific phage cocktail in naïve mice, this did in fact not negatively affect the efficiency of the phages in a wound infection model [ 60 ]. Antibody formation and neutralizing capacity depend on the phage type, especially the capsid and tail protein composition; therefore, phages vary in immunogenicity and can induce different antibody responses [ 58 , 59 , 67 ]. In a murine study, Chechushkov et al [ 67 ] found that phages with podovirus morphotype were non-immunogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody formation and neutralizing capacity depend on the phage type, especially the capsid and tail protein composition; therefore, phages vary in immunogenicity and can induce different antibody responses [ 58 , 59 , 67 ]. In a murine study, Chechushkov et al [ 67 ] found that phages with podovirus morphotype were non-immunogenic. In contrast, they observed an increase in neutralizing antibodies after triple immunization with phages of myovirus and siphovirus morphotypes [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo experiments demonstrated that phages can reduce the bacterial load and weight of abscesses ( Capparelli et al, 2007 ). At the same time, increasing evidence suggests that phages may have a major impact on the immune system by interacting with macrophages, neutrophils, and T-cell polarization ( Chechushkov et al, 2021 ). Phage therapy as a potential regimen against drug-resistant bacteria still requires adequate clinical trials.…”
Section: Discussionmentioning
confidence: 99%